Do cholesterol-lowering drugs influence on bone metabolism? - Sewerynek, Ewa; Stuss, Michał (Menopause Review/Przegląd Menopauzalny, 2006)
Statins, without any doubt, belong to the most effective lipid-lowering drugs. For almost 30 years they have been successfully administered to hypercholesterolemic patients. A large number of clinical trials confirm that statin treatment significantly improves the prognosis for patients after myocardial infarction. The results of research from the last decade show that administration of this class of drugs is highly beneficial, causing versatile effects. They have antiaggregational, fibrinolytic and anti-inflammatory effects. Due to the inhibition of blood-vessel constriction, they cause vasodilatation. Statins influence angiogenesis and work as antineoplastic agents. By synapto- and neurogenesis stimulation, they inhibit neurodegeneration and development of dementia. Do HMG-CoA inhibitors influence bone metabolism? Is it a beneficial effect? Results of experimental research suggest that, due to inducing higher bone formation, statins prevent diseases caused by bone mass losing. A large number of clinical trials confirm this information. In observational studies, the usage of statins diminishes the risk of hip fracture, providing bone mass increase in the hip. According to the present data, this class of drugs has no effect on either spine mineral density or on the risk of its fracture. These could be regarded as additional clinical implications for hypercholesterolemic patients but further, large population-based, randomized, controlled trials are needed to confirm the presented results.